YES Problem: a(b(x)) -> b(a(a(x))) b(c(x)) -> c(b(b(x))) c(a(x)) -> a(c(c(x))) u(a(x)) -> x v(b(x)) -> x w(c(x)) -> x a(u(x)) -> x b(v(x)) -> x c(w(x)) -> x Proof: Arctic Interpretation Processor: dimension: 1 interpretation: [w](x0) = 7x0, [v](x0) = 10x0, [u](x0) = 14x0, [c](x0) = x0, [a](x0) = x0, [b](x0) = x0 orientation: a(b(x)) = x >= x = b(a(a(x))) b(c(x)) = x >= x = c(b(b(x))) c(a(x)) = x >= x = a(c(c(x))) u(a(x)) = 14x >= x = x v(b(x)) = 10x >= x = x w(c(x)) = 7x >= x = x a(u(x)) = 14x >= x = x b(v(x)) = 10x >= x = x c(w(x)) = 7x >= x = x problem: a(b(x)) -> b(a(a(x))) b(c(x)) -> c(b(b(x))) c(a(x)) -> a(c(c(x))) String Reversal Processor: b(a(x)) -> a(a(b(x))) c(b(x)) -> b(b(c(x))) a(c(x)) -> c(c(a(x))) Matrix Interpretation Processor: dim=3 interpretation: [1 0 0] [c](x0) = [0 0 0]x0 [0 0 0] , [1 0 0] [1] [a](x0) = [0 0 1]x0 + [1] [0 1 0] [1], [1 1 1] [b](x0) = [0 1 1]x0 [0 1 1] orientation: [1 1 1] [3] [1 1 1] [2] b(a(x)) = [0 1 1]x + [2] >= [0 1 1]x + [2] = a(a(b(x))) [0 1 1] [2] [0 1 1] [2] [1 1 1] [1 0 0] c(b(x)) = [0 0 0]x >= [0 0 0]x = b(b(c(x))) [0 0 0] [0 0 0] [1 0 0] [1] [1 0 0] [1] a(c(x)) = [0 0 0]x + [1] >= [0 0 0]x + [0] = c(c(a(x))) [0 0 0] [1] [0 0 0] [0] problem: c(b(x)) -> b(b(c(x))) a(c(x)) -> c(c(a(x))) String Reversal Processor: b(c(x)) -> c(b(b(x))) c(a(x)) -> a(c(c(x))) Matrix Interpretation Processor: dim=3 interpretation: [1 1 1] [c](x0) = [0 1 0]x0 [0 0 1] , [1 0 0] [1] [a](x0) = [0 1 1]x0 + [1] [0 1 1] [0], [1 0 0] [b](x0) = [0 0 0]x0 [0 1 1] orientation: [1 1 1] [1 1 1] b(c(x)) = [0 0 0]x >= [0 0 0]x = c(b(b(x))) [0 1 1] [0 1 1] [1 2 2] [2] [1 2 2] [1] c(a(x)) = [0 1 1]x + [1] >= [0 1 1]x + [1] = a(c(c(x))) [0 1 1] [0] [0 1 1] [0] problem: b(c(x)) -> c(b(b(x))) KBO Processor: weight function: w0 = 1 w(c) = 1 w(b) = 0 precedence: b > c problem: Qed